2019
DOI: 10.1007/s11695-019-03942-0
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Post-operative Complications in Super-Super Obesity Compared to Super Obesity in Accredited Bariatric Surgery Centers

Abstract: Background The prevalence of super obesity (SO, BMI > 50.0 kg/m 2) and super-super obesity (SSO, BMI > 60 kg/m 2) is increasing. Current data are limited and discrepant on the relationship between SSO and post-bariatric surgery complication risk. We hypothesized there would be increased complications for both laparoscopic Roux-en-Y gastric bypass (LRYGB) and sleeve gastrectomy (LSG) in SSO compared to SO, but the relative risk (RR) would support the use of LSG in SSO patients. Methods Metabolic and Bariatric S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 14 publications
1
16
0
2
Order By: Relevance
“…This survey found that 72.2% of surgeons favored postoperative prophylactic anticoagulation for at least 2 weeks (up to 6 weeks). This practice is supported by published data by Wilkinson et al [75] and Nasser et al [76], who reported higher incidences of DVT/PTE among patients with BMI superior to 50 kg/m 2 . In addition, Stier et al demonstrated that patients with morbid obesity (at least those with BMI greater than 50 kg/m 2 ) treated with routine prophylactic enoxaparin did not achieve the defined target range for aFXa [77].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This survey found that 72.2% of surgeons favored postoperative prophylactic anticoagulation for at least 2 weeks (up to 6 weeks). This practice is supported by published data by Wilkinson et al [75] and Nasser et al [76], who reported higher incidences of DVT/PTE among patients with BMI superior to 50 kg/m 2 . In addition, Stier et al demonstrated that patients with morbid obesity (at least those with BMI greater than 50 kg/m 2 ) treated with routine prophylactic enoxaparin did not achieve the defined target range for aFXa [77].…”
Section: Discussionsupporting
confidence: 71%
“…Both studies divided patients into BMI greater than 50 kg/m 2 and BMI greater than 60 kg/ m 2 . Wilkinson et al [75] analyzed the outcomes of over 30,000 patients with BMI over 50 kg/m 2 and Nasser et al [76] analyzed the outcomes of over 85,000 patients BMI over 50 kg/m 2 . Both studies confirmed that the frequency of unplanned ICU care was higher than for patients with severe obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric and metabolic surgery meets wide acceptance with an acceptable perioperative risk profile even in patients with higher perioperative risk profiles. Especially super-super obese (SSO) patients with a Body-Mass-Index (BMI) > 60 kg/m 2 are prone to operation risks and morbidity [1][2][3], caused by difficulties in exposure, a fatty liver, tension on the surgical instruments and co-existing comorbidities [4][5][6]. Therefore, operation time, length of hospital stay, and complication rates have been described to be higher in SSO patients in comparison to patients with a BMI < 60 kg/m 2 [1,3].…”
mentioning
confidence: 99%
“…После проведения подготовительных мероприятий встаёт вопрос о выборе оптимального метода хирургического лечения. Возможно применение как рестриктивных, так и комбинированных операций, при этом сторонники первого типа вмешательств отмечают меньшие анестезиологические и операционные риски в сравнении с операциями с мальабсорбтивным компонентом [15]. Однако имеются данные, показывающие также меньшее влияние этого типа операций на снижение избыточной массы тела и регресс коморбидной патологии.…”
Section: Review Of Literatureunclassified